2017
DOI: 10.1016/j.engstruct.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Material properties and compressive local buckling response of high strength steel square and rectangular hollow sections

Abstract: An experimental investigation into the structural performance of compressed high strength steel (HSS) square and rectangular hollow sections is described in this paper. Both hot-rolled and cold-formed HSS sections were examined. In total six S460NH and five S690QH hot-rolled section sizes and three S500MC, two S700MC and four S960QC cold-formed section sizes were tested. The experimental programme comprised tensile coupon tests on flat and corner material, measurements of geometric imperfections, full cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 32 publications
4
65
0
Order By: Relevance
“…Similar conservatism is also observed for the bending test results on the lower grade materials [45,51,52]. However, a stricter Class 3 limit of 38 was proposed in [49] for the case of ordinary carbon steel sections, based on the results of stub column tests; this limit was also shown to be suitable for high strength steels in [35]. Adoption of the proposed Class 3 limit of 38 is therefore supported in this study.…”
Section: Class 3 Slenderness Limitsupporting
confidence: 52%
See 2 more Smart Citations
“…Similar conservatism is also observed for the bending test results on the lower grade materials [45,51,52]. However, a stricter Class 3 limit of 38 was proposed in [49] for the case of ordinary carbon steel sections, based on the results of stub column tests; this limit was also shown to be suitable for high strength steels in [35]. Adoption of the proposed Class 3 limit of 38 is therefore supported in this study.…”
Section: Class 3 Slenderness Limitsupporting
confidence: 52%
“…Similarly, the stricter Class 2 limit of 34 proposed in [49] was shown to be more suitable than the current codified limit of 38 for high strength steel internal elements in compression. Finally, while the current codified Class 3 limit of 42 was found to be applicable to high strength steel internal elements in compression on the basis of the presented bending tests, the results of stub column tests on high strength steel hollow sections in [35] revealed that a lower value of 38 [49] is more appropriate, and is therefore recommended herein. Overall, the behavioural trends exhibited by the examined high strength steel beams follow those observed for lower grades of material, and the results presented herein support the adoption of the revised slenderness limits proposed in [49] in Eurocode 3 for both normal and high strength steels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the deviation of the experimental results from the theoretical resistance increases with slenderness, while the tendency directs to more and more optimistic results. This could be also found for cold-formed sections [20]. Another observation is the generally better performance of the experiments conducted by the authors of this paper.…”
Section: Local Buckling Resistance Prediction Using the Effective Widsupporting
confidence: 78%
“…Hence, their suitability to HSS needs to be evaluated. Complementing the existing literature that investigates the structural performance of HSS [1][2][3][4][5][6], the present paper examines the structural behaviour of stub columns subjected to biaxial bending and compression that has been left relatively unexplored. Focus is placed upon the performance of S460 and S690 hot-finished square and rectangular hollow sections.…”
Section: Introductionmentioning
confidence: 99%